Peningkatan Hasil Belajar pada Materi Refleksi Berbantuan Geogebra - Awiyadi, Badai Purwa; Napitupulu, Bettisari; Ismail, Raoda (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2026)
This study aims to improve students' cognitive learning outcomes, conceptual understanding, and learning activities through the implementation of the Guided Discovery Learning (GDL) model assisted by GeoGebra. The study used a Classroom Action Research (CAR) approach implemented in two cycles, each including planning, action implementation, observation, and reflection, with 30 students of class XI-A of SMA Negeri 1 Edera as subjects. Data were collected through learning outcome tests and observations of student activities, then analyzed descriptively quantitatively and qualitatively. The results showed an increase in the average value of student learning outcomes from 49.58 in Cycle I to 84.42 in Cycle II, as well as an increase in classical learning completeness from 20% to 86.67%. Students' conceptual understanding increased, indicated by the ability to explain changes in coordinates resulting from reflection and distinguish reflections on axes and lines more precisely. Students' learning activities also increased from the active category to very active. Thus, it can be concluded that the implementation of the Guided Discovery Learning model assisted by GeoGebra is effective in improving the quality of the process and results of mathematics learning on reflection material. Keywords: Student Activities, GeoGebra, Learning Outcomes, Reflection